Agricultural land use change impacts soil CO2 emission and its 13C-isotopic signature in central China - Zhang, Qian; Wu, Junjun; Lei, Yao; Yang, Fan; Zhang, Dandan; Zhang, Kerong; Zhang, Quanfa; Cheng, Xiaoli (Soil & tillage research, 2018)
•The conversion cropland to afforested land significantly increased soil CO2 flux.•The conversion cropland to afforested land lowered the δ13C of soil CO2.•Variation in δ13C of soil-respired CO2 depended on change in soil substrate.•δ13C of soil-respired CO2 was positively correlated with δ13C of microbial biomass. Land use change has been widely considered as a key driver of global carbon (C) dynamics. However, the impact of agricultural land use change on soil respiration and its 13C-isotopic signature of CO2 are not fully understood. Therefore, we conducted a field experiment to investigate the seasonal variation of soil CO2 flux and its 13C-isotopic signature and their relationships with biotic factors and abiotic factors under land use conversion from croplands to afforested land (woodland and shrubland) after 30 years. Measurement of CO2 flux was conducted once a month for a whole year. The results showed that the conversion cropland to afforested land significantly increased soil CO2 flux and lowered the δ13C of soil CO2. The soil CO2 flux showed similar seasonal patterns among land use types with the highest (994.87 mg m−2 h−1) in summer and the lowest (25.53 mg m−2 h−1) in winter. The soil CO2 flux was positively related to soil organic C and labile C of topsoil (0–10 cm), as well as soil temperature, whereas the δ13C of soil CO2 emission was positively correlated with the δ13C of microbial biomass and negatively correlated with soil temperature. Overall, our results reveal that subject to long-term land use change, soil CO2 fluxes significantly increase in afforested land due to improved availability of soil C, and its 13C-isotopic signature are strongly related to isotope signature of plant litter inputs.